2013
DOI: 10.1097/hpc.0b013e31829e005d
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented QRS Complexes—A Novel but Underutilized Electrocardiograhic Marker of Heart Disease

Abstract: The electrocardiogram is the mainstay approach for diagnosing a myocardial infarction (MI). The diagnosis of an old MI and the identification of myocardial scar via the electrocardiogram are difficult because there are no other specific signs for a non-Q-wave MI. In this article, we will review the fragmented QRS and its role in identifying myocardial scar and depolarization abnormalities in patients with coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 25 publications
0
30
0
1
Order By: Relevance
“…Myocardial fibrosis may disrupt QRS morphology and lead to fragmentation of QRS on 12-lead ECG. Accordingly, prevalence of fQRS is relatively low among the healthy general population [22] and relatively high in patients with myocardial fibrosis or scarring [11,12,13,14,23]. These data suggest that fQRS may be a useful tool for the assessment of myocardial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial fibrosis may disrupt QRS morphology and lead to fragmentation of QRS on 12-lead ECG. Accordingly, prevalence of fQRS is relatively low among the healthy general population [22] and relatively high in patients with myocardial fibrosis or scarring [11,12,13,14,23]. These data suggest that fQRS may be a useful tool for the assessment of myocardial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of formation of the fQRS can be explained by significant scarring and necrosis of the myocardium (Zipes and Das, 2009; Fares et al, 2013; Jain et al, 2014). In 2006 Das et al proved by myocardial single photon emission tomography (SPECT) in a population of patients referred to a nuclear stress test that the presence of fQRS correlates to a regional myocardial scar and the sensitivity of fQRS to detect myocardial scar is significantly greater (85.6%) than the sensitivity the Q wave has (36.3%) (Das et al, 2006).…”
Section: Backgroundsmentioning
confidence: 99%
“…However, some of the pathologic processes that result in fQRS are reversible. Among the scarred tissue there can be regions of viable myocardial tissue (Zipes and Das, 2009; Fares et al, 2013) and ischemia decelerates the conduction velocity in the peri-infarct zone (Mann et al, 2015). It has been shown that fQRS may diminish from the ECG during a cardiac rehabilitation program after a STEMI and patients with hypertension (Bulut et al, 2015).…”
Section: Backgroundsmentioning
confidence: 99%
See 2 more Smart Citations